ANALISA LAJU KOROSI KETEBALAN PIPA BAJA KARBON PADA PROSES PEMBAKARAN DI UNIT BOILER - Darmadi, Herry; Nelza, Novia; Muhammad Iqbal Harapan Muslim Siregar; Kurnia, Dian; Yudhi Bastanta (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
The demand for electrical energy continues to increase along with the increase in economic growth in Indonesia, where currently almost all equipment used by humans depends on electrical energy. The steam power generation system is one of the power generation systems that are commonly used in industries and other power plants. In general, a steam power generation system consists of several main components, namely: pumps, steam turbines, boilers, generators and condensers. Boilers are composed of several components such as pipes, chimneys, superheaters, steam drums, economizers, and other important components. One of the most important components in the boiler system is the boiler pipe which plays a role in helping the combustion process to be used in the boiler. Loss of boiler pipe thickness due to corrosion is one of the important factors that really need to be considered in the boiler combustion process at PLTU. Loss of thickness of the boiler pipe in the combustion process that is too large can cause pipe leakage which results in the interruption of the combustion process in the boiler pipe. So to overcome this problem, checks are carried out to carry out maintenance on the boiler pipe to avoid leaks in the boiler pipe. After the calculation, the average reduction in pipe thickness due to corrosion is 0.1465 mm/yr